Model Pola Asuh Islami Sebagai Solusi Untuk Meningkatkan Motivasi Belajar Anak Usia Dini - Wanati; Anisza Anisza; Nur Kholik Affandi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
In the world of education, low learning motivation in early childhood is a significant issue. This is particularly true for early character formation. Parenting styles that are less than ideal and not aligned with spiritual principles are among the factors contributing to this condition. This article focuses on how Islamic parenting models can help increase early childhood learning motivation. Islamic parenting is considered a comprehensive religious approach and educational strategy in the current discourse. This study is based on Islamic educational theory and child development psychology and uses a qualitative, descriptive-analytical approach. Data were collected through literature research and observations of parenting practices. The results indicate that increasing children's intrinsic motivation to learn can be achieved by implementing Islamic parenting styles that include role models, worship habits, and continuous affection. Furthermore, it has been shown that incorporating spiritual values ​​helps children become more disciplined and responsible. Therefore, it can be concluded that Islamic parenting models are a useful and relevant option for sustainably increasing early childhood learning motivation.